2015
DOI: 10.1158/0008-5472.can-14-2285
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal and Familial Risk Factors for Brain Tumors in Childhood through Young Adulthood

Abstract: Perinatal factors including high birth weight have been associated with childhood brain tumors in case-control studies. However, the specific contributions of gestational age and fetal growth remain unknown, and these issues have never been examined in large cohort studies with follow-up into adulthood. We conducted a national cohort study of 3,571,574 persons born in Sweden in 1973–2008, followed up for brain tumor incidence through 2010 (maximum age 38 years) to examine perinatal and familial risk factors. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 44 publications
3
40
1
1
Order By: Relevance
“…Unlike previous recent studies conducted in the United States, Scandinavia and United Kingdom 5 which all used data linkage and an earlier meta‐analysis of eight studies (five of which used data linkage), we found no evidence to support our first hypothesis that the risk of CBT or any of its subtypes would be increased by high fetal growth or high birth weight. Nevertheless, our findings were similar to two case‐control studies, that is, a multinational study for birth weight and an Australian study for birth weight, appropriateness of birth weight and POBW.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Unlike previous recent studies conducted in the United States, Scandinavia and United Kingdom 5 which all used data linkage and an earlier meta‐analysis of eight studies (five of which used data linkage), we found no evidence to support our first hypothesis that the risk of CBT or any of its subtypes would be increased by high fetal growth or high birth weight. Nevertheless, our findings were similar to two case‐control studies, that is, a multinational study for birth weight and an Australian study for birth weight, appropriateness of birth weight and POBW.…”
Section: Discussioncontrasting
confidence: 99%
“…The association between extremes of birth weight and CBT has been frequently investigated. Of nine papers published since 2010, the majority reported a positive association with higher birth weight, for either all CBT combined or at least one subtype, most commonly astrocytoma and one with lower birth weight . However, this apparent weight of evidence includes case populations from similar geographical areas with at least some overlapping diagnosis years with three from Scandinivia, three from California, and two from Texas …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reported a summary OR of 1.38 (95% CI 1.07–1.79) for individuals with birth weights >4000 versus ≤4000 g [13]. A population-based Swedish registry linkage study also examined associations between birth weight and astrocytoma subtypes in individuals whose brain tumors were diagnosed in childhood through younger adulthood (≤38 years), finding that individuals with birth weights >4000 versus 2500–3999 g had a significant increased risk for pilocytic astrocytomas specifically, but not for other astrocytomas, medulloblastomas, or ependymomas [19]. These results are consistent with our findings for NF1-OPGs, a glial neoplasm classified as a pilocytic astrocytoma of the optic nerve, chiasm, or tract [20].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have linked season of birth with a wide variety of conditions including lifespan and mortality risk [35], cardiovascular events [2, 6], type II diabetes [7], hypertension [8], mental health conditions [9], and suicide risk [10]. An association with season of birth has also been identified in malignant conditions such as childhood and adolescent haematological [1113] and central nervous system cancers [14]. …”
Section: Introductionmentioning
confidence: 99%